2014
DOI: 10.1007/s11135-014-0142-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multidimensional top management support on project success: an empirical investigation

Abstract: During the last three decades, substantial research has been conducted with top management support as a single dimensional construct. The significance of top management support as a critical success factor is well recognized in the literature. Yet, top management support has rarely been used as a multidimensional construct to measure project success. This paper examines the effect of multidimensional top management support on project success through cross-sectional data collected from 208 project management pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 96 publications
5
38
0
Order By: Relevance
“…For this purpose, the authors developed and validated the Top Management Support Questionnaire (TMSQ) as reported in Ahmed et al (2016). The scale development process for measurement of a five-dimensional construct of top management support included item creation, item sorting, instrument testing, and instrument validation processes, adapted from earlier studies (Akter, D'Ambra, & Ray, 2013;Amundsen & Martinsen, 2014;Schmiedel, Vom, & Recker, 2014).…”
Section: Measurement Scalementioning
confidence: 99%
See 4 more Smart Citations
“…For this purpose, the authors developed and validated the Top Management Support Questionnaire (TMSQ) as reported in Ahmed et al (2016). The scale development process for measurement of a five-dimensional construct of top management support included item creation, item sorting, instrument testing, and instrument validation processes, adapted from earlier studies (Akter, D'Ambra, & Ray, 2013;Amundsen & Martinsen, 2014;Schmiedel, Vom, & Recker, 2014).…”
Section: Measurement Scalementioning
confidence: 99%
“…Summary of Demographic Data (Ahmed et al, 2016). In agreement with Hair et al (2010), demographic variables were entered concurrently in the regression model during the first step.…”
Section: Testing Of Research Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations